2023
DOI: 10.1186/s13054-023-04704-2
|View full text |Cite
|
Sign up to set email alerts
|

Serial assessments of cardiac output and mixed venous oxygen saturation in comatose patients after out-of-hospital cardiac arrest

Johannes Grand,
Christian Hassager,
Henrik Schmidt
et al.

Abstract: Aim To assess the association with outcomes of cardiac index (CI) and mixed venous oxygen saturation (SvO2) in comatose patients resuscitated from out-of-hospital cardiac arrest (OHCA). Methods In the cohort study of 789 patients included in the “BOX”-trial, 565 (77%) patients were included in this hemodynamic substudy (age 62 ± 13 years, male sex 81%). Pulmonary artery catheters were inserted shortly after ICU admission. CI and SvO2 were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…7 The BOX investigators have demonstrated in another analysis of their trial that the first mixed venous oxygen saturation after resuscitation from OHCA was inversely associated with mortality and renal failure. 8 It is, therefore, somewhat disturbing that the higher MAP target in patients with heart failure was associated with a 2.73 higher odds for the need of renal replacement therapy; yet the current analysis was grossly underpowered to assess this end point. Trends in lactate, urine output, or biomarkers for organ dysfunction offer important complementary information to help interpretation of hemodynamics.…”
Section: See Article By Grand Et Almentioning
confidence: 86%
“…7 The BOX investigators have demonstrated in another analysis of their trial that the first mixed venous oxygen saturation after resuscitation from OHCA was inversely associated with mortality and renal failure. 8 It is, therefore, somewhat disturbing that the higher MAP target in patients with heart failure was associated with a 2.73 higher odds for the need of renal replacement therapy; yet the current analysis was grossly underpowered to assess this end point. Trends in lactate, urine output, or biomarkers for organ dysfunction offer important complementary information to help interpretation of hemodynamics.…”
Section: See Article By Grand Et Almentioning
confidence: 86%
“…In patients with cardiac arrest, the weakened myocardium could be more prone to post-OHCA myocardial dysfunction. CI is not associated with clinical outcomes 30,[33][34][35] ; however, the response of this myocardium to increased afterload and vasopressor stress, indicated by changes in CI with higher vasopressor doses, provides valuable mechanistic insights. Although the sample size is small for conclusive clinical outcomes, this information is hypothesis generating for future hemodynamic studies of effects of MAP and vasopressor manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…29 A previously investigated interobserver variation demonstrated low bias and high reproducibility. 30 In Odense, continuous cardiac output measurement was obtained through intermittent blood heating, with the response detected by a thermistor located at the catheter's tip. 31 Previous studies have shown excellent correlation, accuracy, and precision among different methods of cardiac output measurement.…”
Section: Intensive Care Monitoring and Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Pilot studies have suggested that higher mean arterial pressure (MAP) post-OHCA, typically achieved using vasopressors like noradrenaline, may reduce brain injury. [7][8][9][10] However, vasopressors carry risks such as cardiac arrhythmias, myocardial ischemia, and increased afterload, and are associated with adverse outcomes. 11 No firm conclusion on the benefits and harms of a lower vs. a higher blood pressure target has been drawn for patients admitted to the ICU after OHCA.…”
Section: Introductionmentioning
confidence: 99%